Pengaruh Sosialisasi dan Pelatihan Terhadap Kinerja Karyawan UMKM di Rumah BUMN BRI Jakarta - Berliana Megasari; Andi Heru Susanto (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to analyse the effect of socialisation and training on employee performance at Rumah BUMN Jakarta. This research is based on the increased knowledge, skills and networks of MSMEs through socialisation and training programmes, which are expected to improve the performance of MSMEs and their contribution to the local and national economy. This study uses a quantitative approach with an online survey technique. Data was collected from 258 respondents who were sampled from a population of 1,000 MSMEs assisted by Rumah BUMN Jakarta. Data analysis used multiple linear regression analysis to test the effect of independent variables (socialisation and training) on the dependent variable (MSME employee performance). The results showed that socialisation and training have a positive and significant influence on employee performance. Simultaneously, both independent variables are significantly related to employee performance. This shows that socialisation and training programmes are effective programmes to improve the performance of MSME employees at Rumah BUMN Jakarta.